E-procurement Furniture Raw Material for Small and Medium Enterprises in Malaysia - Samsudin, Mohd Elfirizal (Universiti Teknologi Petronas, 2006)
Due to rapid advancement of electronic commerce and web technologies in recent years, the concepts and such applications have been significantly extended. This research will look deeply into the e-procurement among the small medium enterprise (SME) and to analyse their most needed and accurate requirement from this type of internet business tools to run the business in Malaysia. The objective is to connect the ideas between business environment (business scope) and the business requirement accurately significantly to create an e-procurement system to provide a conductive platform for product requisition, payment transaction, discussion, assistance, cooperation and coordination between responsible vendors and serious customer including private sectors, regional and international organizations. One of the main challenges is there nowadays there's a lot of existing procurement system online involve, it is important to research and analyst this existing systems to extract the main idea and compare it with the project objective and requirement to finally discuss the best ideas that is required for the proposed system. In this project, several techniques have been used starting with ideas and information research and gathering that have been done through journals, existing paper work, and previous systems that create by previous students. For the products (furniture raw materials) information and attributes, considerable survey has been done through the internet and magazine and also from the products questionnaire. Based on all the research and findings, finally a working system (prototype) of an E-Procurement intermediary for SME specifically on furniture raw materials should be implemented and to be the best solution that satisfied all parties.